2019
DOI: 10.1177/1073191119842255
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the SNAP-IV in Children Displaying ADHD Symptoms

Abstract: The Swanson, Nolan, and Pelham Rating Scale (SNAP-IV) is a widely used scale that measures the core symptoms of attention deficit hyperactivity disorder (ADHD). However, there are contradictory findings regarding factor structure. Factor structure and measurement equivalence/invariance analysis on parent and teacher SNAP-IV for children referred for an ADHD assessment ( N = 250; 6-17 years), revealed a two-factor structure provided the best fit. SNAP-IV scores were also compared with clinician diagnosis of ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 35 publications
0
75
0
Order By: Relevance
“…Children with anxiety and those with ADHD may also have differences in their responses to unpredicted stimuli [Cornwell, Garrido, Overstreet, Pine, & Grillon, 2017; Gonzalez‐Gadea et al, 2015]. Given the high prevalence of these conditions in children with ASD [Avni, Ben‐Itzchak, & Zachor, 2018], the Screen for Child Anxiety Related Disorders (SCARED‐parent version) (individuals 8–18) [Birmaher et al, 1999] and Swanson, Nolan, and Pelham (SNAP‐IV) (individuals 6–18) [Hall et al, 2020] were used to account for these as possible confounders. Detailed medical history was collected for all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Children with anxiety and those with ADHD may also have differences in their responses to unpredicted stimuli [Cornwell, Garrido, Overstreet, Pine, & Grillon, 2017; Gonzalez‐Gadea et al, 2015]. Given the high prevalence of these conditions in children with ASD [Avni, Ben‐Itzchak, & Zachor, 2018], the Screen for Child Anxiety Related Disorders (SCARED‐parent version) (individuals 8–18) [Birmaher et al, 1999] and Swanson, Nolan, and Pelham (SNAP‐IV) (individuals 6–18) [Hall et al, 2020] were used to account for these as possible confounders. Detailed medical history was collected for all participants.…”
Section: Methodsmentioning
confidence: 99%
“…(Cornwell, Garrido, Overstreet, Pine, & Grillon, 2017;Gonzalez-Gadea et al, 2015). Given the high prevalence of these conditions in children with ASD (Avni, Ben-Itzchak, & Zachor, 2018), the Screen for Child Anxiety Related Disorders (SCARED-parent version) (individuals 8-18) (Birmaher et al, 1999) and Swanson, Nolan, and Pelham (SNAP-IV) (individuals 6-18) (Hall et al, 2019) were used to account for these as possible confounders. Detailed medical history was collected for all participants.…”
Section: Participants and Phenotypic Characterizationmentioning
confidence: 99%
“…Interestingly, we found that almost all oppositional questions from the teacher report were categorized into the high-order group, whereas oppositional questions from the parent report were in the low-order group (67). That is, according to these internationally well-known standardized scales used in our ADHD studies, teacher reports of oppositional symptoms had better discriminant validity in distinguishing ADHD from non-ADHD.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, through the process of this deep learning approach, we can rank the questions of the rating scales in terms of the ability of the machine to learn from the data and to predict the missing values accurately. We hypothesized that questions assessing hyperactivity-impulsivity behaviors, particularly from teacher reports, would have high imputation accuracy and discriminating ability based on previous studies suggesting that these symptoms are observable (67) and that teachers may have more opportunities to observe ADHD-related behaviors such as oppositional defiant symptoms than parents do (35).…”
Section: Introductionmentioning
confidence: 99%